2006
DOI: 10.1007/s11284-006-0056-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring wild greenfinch (Carduelis chloris) for Salmonella enterica typhimurium

Abstract: The identification and monitoring of emerging infectious diseases in free living wild birds is a challenge to wildlife biologists. In this study, a non-invasive methodology for identifying salmonellosis in wild garden birds was developed. We focussed on greenfinch, Carduelis chloris, which were found to have a seasonal pattern in the occurrence of Salmonella Typhimurium DT 56(v). Principal components analysis of biometric data indicated that low fat and low weight could be useful indicators of Salmonella posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…However, the numbers of incidents and cases of salmonellosis in greenfinches in winter far outweighed those in chaffinches, indicating a real predisposition of the greenfinch to this disease in Britain. This concurs with other reports which identified the greenfinch as the species most frequently affected by salmonellosis in Great Britain (Wilson and Macdonald, 1967;Routh and Sleeman, 1995;Pennycott et al, 1998;Grant et al, 2007).…”
Section: Garden Bird Speciessupporting
confidence: 92%
See 1 more Smart Citation
“…However, the numbers of incidents and cases of salmonellosis in greenfinches in winter far outweighed those in chaffinches, indicating a real predisposition of the greenfinch to this disease in Britain. This concurs with other reports which identified the greenfinch as the species most frequently affected by salmonellosis in Great Britain (Wilson and Macdonald, 1967;Routh and Sleeman, 1995;Pennycott et al, 1998;Grant et al, 2007).…”
Section: Garden Bird Speciessupporting
confidence: 92%
“…A recent study that combined fecal screening of sick birds with postmortem examination of carcasses recovered from a single site in Scotland found that poor body fat scores and low body weight were useful field indicators to identify greenfinches with S. Typhimurium DT56(v) infection (Grant et al, 2007).…”
Section: Garden Bird Speciesmentioning
confidence: 99%
“…PFGE band profiles are shown, and the scale indicates percent similarity. (7,26). While the number of isolates each year will be influenced by the overall number of salmonellosis incidents, variation in the intensity of opportunistic surveillance, coupled with the transition between single and dual surveillance schemes, might have altered the efficiency of reporting over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…birds affected by disease. This is especially relevant for greenfinches due to the current prevalence of the parasite Trichomonas gallinae (Robinson et al 2010) as well as the greenfinches' susceptibility to Salmonella infections (Refsum et al 2003, Grant et al 2007. Considering that the average ω-6/ω-3 ratio in the blood of greenfinches in our study was 76:1, it is possible that such high levels of ω-6 could aggravate the already poor health condition of infected birds.…”
Section: Discussionmentioning
confidence: 83%